Effect of Some Growth Factors on Protease Production by Rhizopus oryzae - Ahmed, Suhad A; Abood, Nagham H (Al-Nahrain Journal of Science, 2017)
The main purpose of the present study was to invistgate different parameters of protease productivity and to optimize basal fermentation conditions for the production of protease enzyme under SSF where the isolated mold Rhizopus oligosporus was used. In this study, the effect of a number of determinants of environmental and nutritional factors in the production of the protein hydrolyzing enzyme (protease) from the isolated mold Rhizopus oryzae also studied. These factors which may play an influential role in improving the production of protease was to focus the source of carbon (flower without seeds) weight, the initial pH of the production medium which ingredients sunflower residue flowers without seeds was taken in conical flask as solid substrate and moistened with mineral solution consisting of 2.0g NH4SO4, 0.3g K2HPO4, 0.5g NaCl, 0.5g MgSO4, 0.2g Na2HPO4 and 0.1g CaCl2 per liter of distilled water. The inoculum size of the mold used in the study, the temperature of incubation and the incubation period. It was found that optimum conditions for protease production in the current study using sunflower residue as a source of carbon weighing 20g where the specific activity (2.83u/mg), optimum pH for the production of the enzyme is 5, has the resulted in the use of size 2×106 spores/ml inoculum to increase the production of the enzyme significantly while the optimum temperature for the production was 30ºC and enzyme production has reached to the maximum (17.41u/mg) after 144hrs of incubation.